Active Modulation of Er3+ Emission Lifetime by VO2 Phase‐Change Thin Films - Boris Kalinic; Tiziana Cesca; Alessandro Lovo; Carlo Scian; Roberto Macaluso; Fabio Bovino; Roberto Li Voti; Concita Sibilia; Giovanni Mattei (Advanced Photonics Research, 2024)
The active modulation of optical response of quantum emitters at the nanoscale is of paramount importance to realize tunable light sources for nanophotonic devices. Herein, a thin film of phase‐change material (VO2) is coupled to a 20 nm‐thick silica layer embedding Er3+ ions, and it is demonstrated how the active tuning of the local density of optical states near the erbium emitters provided by the thermally induced semiconductor‐to‐metal transition of VO2 can be used to dynamically control the Er3+ emission lifetime at telecom wavelength (1.54 μm). A decay rate contrast of a factor 2 is obtained between high temperature (90 °C), when VO2 is metallic, and room temperature, when VO2 is semiconductor, in agreement with calculations performed with the classical dipole oscillator analytical model. A hysteretic behavior is observed by measuring the Er3+ lifetime as a function of the temperature, whose parameters are consistent with those of grazing incidence X‐ray diffraction and optical transmittance measurements. The fractions of Er3+ ions that couple with VO2 in each phase at the different temperatures are determined by the analysis of the temporal decays. The results make the investigated system an optimal candidate for the development of tunable photon sources at telecom wavelength.